2012
DOI: 10.1371/journal.pone.0041281
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease-Induced Cardiac Fibrosis Is Ameliorated by Reducing Circulating Levels of a Non-Dialysable Uremic Toxin, Indoxyl Sulfate

Abstract: Cardiovascular death commonly occurs in patients with chronic kidney disease. Indoxyl sulfate (IS), a uremic toxin, has been demonstrated in vitro as a contributory factor in cardiac fibrosis, a typical pathological finding in uremic cardiomyopathy. This study aimed to determine if cardiac fibrosis is reversible by lowering serum IS levels using an oral charcoal adsorbent, AST-120. Subtotal-nephrectomized (5/6-STNx) Sprague-Dawley rats were randomized to receive either AST-120 (AST-120, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 46 publications
5
108
0
1
Order By: Relevance
“…NADPH oxidases are major sources of reactive oxygen species, and activation of NADPH oxidases was associated with the incidence of AF 29, 30, 31, 32, 33, 34, 35, 36. Furthermore, several studies demonstrated that oxidative stress plays an important role in renal dysfunction–induced cardiac fibrosis, and AST‐120 prevented cardiac damage by alleviating oxidative stress 13, 15. In the present study, expression of NOX2, a membrane‐spanning subunit of NADPH oxidases, and NOX4, which is predominantly localized in the mitochondria, was significantly upregulated in LA tissue isolated from 5/6Nx rats, and the expression of MDA was concomitantly upregulated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NADPH oxidases are major sources of reactive oxygen species, and activation of NADPH oxidases was associated with the incidence of AF 29, 30, 31, 32, 33, 34, 35, 36. Furthermore, several studies demonstrated that oxidative stress plays an important role in renal dysfunction–induced cardiac fibrosis, and AST‐120 prevented cardiac damage by alleviating oxidative stress 13, 15. In the present study, expression of NOX2, a membrane‐spanning subunit of NADPH oxidases, and NOX4, which is predominantly localized in the mitochondria, was significantly upregulated in LA tissue isolated from 5/6Nx rats, and the expression of MDA was concomitantly upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were assigned randomly to the following groups: sham plus vehicle (VEH), sham plus AST‐120, 5/6Nx plus VEH, and 5/6Nx plus AST‐120. VEH and AST‐120 were administered by mixing in standard rat chow at 8% wt/wt for 4 weeks 15. Rats were anesthetized by intraperitoneal injection of a mixture of ketamine (60 mg/kg) and xylazine (10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoxyl sulphate has been found to impair antioxidant mechanisms in cells and promote free radical formation in renal tubular cells and glomerular mesangial cells. Orally administered probiotics containing non-indole-producing bacteria as well as AST-120, an indole absorbing compound, were found to be beneficial in the treatment of patients with kidney disease [31].…”
Section: Indolesmentioning
confidence: 99%
“…Heart failure development [48] Indoles Intracellular signalling, biofilm formation, antibiotic resistance in bacteria [30] Accumulation in patients with CKD [9] Impairment of antioxidation and promotion of free radical formation [9] Promotion of endothelium dysfunction: decreased production of nitric oxide, increased production of reactive oxygen species [9] Hypertrophy of cardiac myocytes and production of collagen by cardiac fibroblasts [32] Decrease of indole concentration is beneficial in CKD [31] Correlation of high concentration of indoxyl sulphate with aortic lesion formation and mortality in CKD [9] Pro-arrhythmogenic potential [9] Association with CV events and mortality in CKD [49] Short-chain fatty acids Energy source of colonic cells and pH regulating agents…”
Section: Gut Bacteria Metabolites Biological/cardiovascular Actions Pmentioning
confidence: 99%